Cardiolipin Synthesis and Outer Membrane Localization Are Required for Shigella flexneri Virulence - Rachael M. Rossi (American Society for Microbiology, 2017)
ABSTRACT Cardiolipin, an anionic phospholipid that resides at the poles of the inner and outer membranes, is synthesized primarily by the putative cardiolipin synthase ClsA in Shigella flexneri. An S. flexneri clsA mutant had no cardiolipin detected within its membrane, grew normally in vitro, and invaded cultured epithelial cells, but it failed to form plaques in epithelial cell monolayers, indicating that cardiolipin is required for virulence. The clsA mutant was initially motile within the host cell cytoplasm but formed filaments and lost motility during replication and failed to spread efficiently to neighboring cells. Mutation of pbgA, which encodes the transporter for cardiolipin from the inner membrane to the outer membrane, also resulted in loss of plaque formation. The S. flexneri pbgA mutant had normal levels of cardiolipin in the inner membrane, but no cardiolipin was detected in the outer membrane. The pbgA mutant invaded and replicated normally within cultured epithelial cells but failed to localize the actin polymerization protein IcsA properly on the bacterial surface and was unable to spread to neighboring cells. The clsA mutant, but not the pbgA mutant, had increased phosphatidylglycerol in the outer membrane. This appeared to compensate partially for the loss of cardiolipin in the outer membrane, allowing some IcsA localization in the outer membrane of the clsA mutant. We propose a dual function for cardiolipin in S. flexneri pathogenesis. In the inner membrane, cardiolipin is essential for proper cell division during intracellular growth. In the outer membrane, cardiolipin facilitates proper presentation of IcsA on the bacterial surface. IMPORTANCE The human pathogen Shigella flexneri causes bacterial dysentery by invading colonic epithelial cells, rapidly multiplying within their cytoplasm, and then spreading intercellularly to neighboring cells. Worldwide, Shigella spp. infect hundreds of millions of people annually, with fatality rates up to 15%. Antibiotic treatment of Shigella infections is compromised by increasing antibiotic resistance, and there is no approved vaccine to prevent future infections. This has created a growing need to understand Shigella pathogenesis and identify new targets for antimicrobial therapeutics. Here we show a previously unknown role of phospholipids in S. flexneri pathogenesis. We demonstrate that cardiolipin is required in the outer membrane for proper surface localization of IcsA and in the inner membrane for cell division during growth in the host cell cytoplasm.